Cryptococcosis in cats: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Pennisi, Maria Grazia; Hartmann, Katrin; Lloret, Albert; Ferrer, Lluis; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hosie, Margaret J; Lutz, Hans; et al.
Overview: Cryptococcosis is worldwide the most common systemic fungal disease in cats; it is caused by the Cryptococcus neoformans– Cryptococcus gattii species complex, which includes eight genotypes and some subtypes (strains) with varying geographical distribution, pathogenicity and antimicrobial susceptibility. Cats acquire the infection from a contaminated environment. The prognosis is favourable in most cases, provided a diagnosis is obtained sufficiently early and prolonged treatment is maintained. Infection: Basidiospores are the infectious propagules of Cryptococcus species as they penetrate the respiratory system and induce primary infection. Asymptomatic colonisation of the respiratory tract is more common than clinical disease. Avian guanos, particularly pigeon droppings, offer favourable conditions for the reproduction of C neoformans . Both Cryptococcus species are associated with decaying vegetation. Disease signs: Cryptococcosis caused by C neoformans or C gattii is indistinguishable clinically. The disease can present in nasal, central nervous system (which can derive from the nasal form or occur independently), cutaneous and systemic forms. Diagnosis: An easy and reliable test for cryptococcosis diagnosis is antigen detection in body fluids. Only isolation and polymerase chain reaction allow identification of the species genotype. Disease management: Amphotericin B, ketoconazole, fluconazole and itraconazole have all been used to treat cats. Surgical excision of any nodules in the skin, nasal or oral mucosa assists recovery. Continued treatment is recommended until the antigen test is negative. Prevention: Efficient preventive measures have not been demonstrated. Vaccines are not available.